Human Resource Management in Realizing Blue Ocean Strategy: A Case Study of Global-Oriented MSMEs - Suwarno Suwarno; Ronal Aprianto (Goodwood Publishing, 2026)
Purpose: This study aims to examine how Strategic Human Resource Management (SHRM), HR Innovation and Creativity, and Global Orientation influence the implementation of the Blue Ocean Strategy among globally oriented MSMEs in Indonesia. Research Methodology: This study used a quantitative approach with an explanatory design. Data were collected through a survey of 154 MSME actors selected using purposive sampling. The analysis employed Structural Equation Modeling-Partial Least Squares (SEM-PLS) using SmartPLS 4.0 software. Results: The findings revealed that Strategic Human Resource Management and Global Orientation significantly and positively affect Blue Ocean Strategy implementation. Meanwhile, HR Innovation and Creativity show a non-significant result, indicating that individual creativity alone cannot drive strategic outcomes without organizational support. Conclusions: Strategic HR practices and a global mindset are key factors for MSMEs to create new market opportunities and support innovative value. Limitations: The study is limited by the sample size and focus on globally oriented MSMEs, which may restrict generalization to other contexts and countries. Contributions: This study contributes to the strategic management and human resource literature in emerging economies and provides practical insights for MSME owners and policymakers to strengthen competitiveness through strategic HR investment.